2014
DOI: 10.1590/s0103-90162014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Univariate and multivariate analysis on processing tomato quality under different mulches

Abstract: The use of eco-friendly mulch materials as alternatives to the standard polyethylene (PE) has become increasingly prevalent worldwide. Consequently, a comparison of mulch materials from different origins is necessary to evaluate their feasibility. Several researchers have compared the effects of mulch materials on each crop variable through univariate analysis (ANOVA).However, it is important to focus on the effect of these materials on fruit quality, because this factor decisively infl uences the acceptance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
6
1
1
Order By: Relevance
“…Total carotenoid content in orange-fleshed tubers was more than three-fold higher compared to sweet potatoes with yellow, purple and white flesh color. The strong interaction between flesh color and total carotenoid content in sweet potato was also presented in study of Ellong, Billard and Adenet ( 2014), Grace et al (2014) and Hussein et al (2014). Within trial in China, Tang, Cai and Xu (2015) found higer total carotenoid in sweet potato tubers compared to results showed in our trial.…”
Section: Kammona Et Al (2015)supporting
confidence: 85%
See 1 more Smart Citation
“…Total carotenoid content in orange-fleshed tubers was more than three-fold higher compared to sweet potatoes with yellow, purple and white flesh color. The strong interaction between flesh color and total carotenoid content in sweet potato was also presented in study of Ellong, Billard and Adenet ( 2014), Grace et al (2014) and Hussein et al (2014). Within trial in China, Tang, Cai and Xu (2015) found higer total carotenoid in sweet potato tubers compared to results showed in our trial.…”
Section: Kammona Et Al (2015)supporting
confidence: 85%
“…The highest vitamin C content was determined in purple cultivars (727.1 mg.kg -1 ), followed by cultivars with white (672.2 mg.kg -1 ) and yellow flesh color (204.7-254.4 mg.kg -1 ). According to study of Ellong, Billard and Adenet (2014), determined vitamin C content in yellow or creme sweet potatoes varied from 177.5 mg.kg -1 to 290.5 mg.kg -1 f. w. It meant higher values of vitamin C content in comparison with our trial. Yildirim, Tokuşoğlu and Öztürk (2011) also stated that cultivar and flesh color had an significant impact on the vitamin C content in sweet potato tubers.…”
Section: Vitamin C Contentcontrasting
confidence: 47%
“…The bigger fruits obtained in grafted Mor-62, together with an intensification of the red colour due to the high lycopene content 39 , might have led to its good visual acceptance. In this context, Di Gioia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lo anterior es el sustento para el proceso de pronóstico de las empresas en el objeto de estudio de esta investigación Como criterios de validez se utilizará la matriz de confusión, el análisis de sensibilidad y especificidad Así mismo, el Análisis Multivariado ha mostrado su importancia en el análisis de problemas en los que intervienen un gran número de variables [13]- [15], representa un conjunto de herramientas estadísticas y matemáticas utilizadas para analizar e interpretar los datos asociadas a múltiples variables [16]. Tiene como finalidad analizar de manera simultánea un conjunto de datos multivariantes medidos para cada individuo u objeto estudiado, lo que permite una mejor comprensión del fenómeno o proceso objeto de estudio [16].…”
Section: Marco Teóricounclassified